Teaching language proficiency through literature and regional cuisines - Toledo Cubillos, Jose Eder
This article arises from the need to think strategies that guide the apprentices to reading and writing as an essential component in the construction of their identity from the regional kitchens. This experience of investigation-actionparticipation, through the hermeneutic approach, allows the construction of narrative texts of their experiences. The question and preoccupation about the linguistic competence in the technical programs of approach of formation for the work are approached, and it allows to think didactic strategies by means of the Colombian Literature that include the education of the regional kitchens.